Micro-Porosity and gas emission characteristics of thermally contacted metamorphic coal by igneous intrusion - Fu, Xiang; Liu, Hongda; Sha, Huihui; Wang, Zhiquan; Liu, Xuan (Frontiers in Earth Science, 2023)
In order to quantitatively characterize the pore structure of thermally contacted metamorphic coal by igneous intrusion and investigate the intrinsic connection between the pore and dispersion properties of coal, the samples of metamorphic coal from different locations of Daxing Coal Mine were collected and processed. The correlative analysis on pore characteristics, including pore area, perimeter, shape factor and fractal dimension of pores with different sizes, were carried out by using scanning electron microscopy (SEM) and pore-fracture analysis system (PCAS). The results show that the porosity of macro- and meso-pores and the number of pores in the metamorphic coal are larger than those of the normal coal. The total length of pores per unit area and the average shape factor increase, and the connectivity of pore is raised, resulting in an enhanced gas release capacity (increased V1) within the first one second. The proportion of gas emission in the first one second of metamorphic coal is much higher than that of other coals. The decrease of pore volume and specific surface area of micropores makes the adsorption capacity weaker, which results in a decrease in the total amount of emission - smaller Δp value, and earlier inflection point and faster attenuation on the emission curve, namely an increased α value. In addition, the V1, α value and volatile content satisfy the quadratic nonlinear and linear relationships, respectively. In the prediction of outburst risk of thermally contacted metamorphic coal, it is more reasonable to use the V1 index to characterize the gas release rate.